The Hollywood spy - MacNeal, Susan Elia (MacNeal, Susan Elia. Maggie Hope mystery, 2021)
"Maggie Hope is off to Hollywood to solve a crime that hits too close to home--and confront the very evil she thought she had left behind in Europe--as the acclaimed World War II mystery series from New York Times bestselling author Susan Elia MacNeal continues. Los Angeles, 1943. As the Allies beat back the Nazis in the Mediterranean and the United States military slowly closes in on Tokyo, Walt Disney cranks out wartime propaganda and the Cocoanut Grove is alive with jazz and swing each night. But behind this sunny façade lies a darker reality. Somewhere in the lush foothills of Hollywood, a woman floats, lifeless, in the pool of one of California's trendiest hotels. When American-born secret agent and British spy Maggie Hope learns that this woman was engaged to her old flame, John Sterling, and that he suspects her death was no accident, intuition tells her he's right. Leaving London under siege--not to mention flying thousands of miles--is a lot to ask. But John was once the love of Maggie's life . . . and she won't say no. Maggie is shocked to find Los Angeles as divided as Europe itself--the Zoot Suit Riots loom large and the Ku Klux Klan casts a long shadow. As she marvels at the hatred in her home country, she can't help but wonder what it will be like to see her lost love once again. But there is little time to dwell on memories once she starts digging into the case. As she traces a web of deception from the infamous Garden of Allah Hotel to the iconic Carthay Theater, she discovers things aren't always the way things appear in the movies--and the political situation in America is more complicated, and dangerous, than the newsreels would have them all believe"--